Real-World Cost of Pediatric Acute Lymphoblastic Leukemia Care Among Commercially Insured Individuals in the United States: Effect of Era and Age at Diagnosis. Issue 11 (27th November 2022) - Turcotte, Lucie M.; Watson, Dave; Tanner, Lynn; Hoover, Alex; Gilchrist, Laura; Finch, Mike; Messinger, Yoav H.
Abstract : PURPOSE: Acute lymphoblastic leukemia (ALL) is the most common pediatric malignancy. Five-year survival is approaching 90%. In efforts to further improve outcomes, it is critical to consider the cost of ALL care. MATERIALS AND METHODS: Commercial insurance data from OptumLabs Data Warehouse were used to identify patients with ALL, age 1-30 years, diagnosed in 1993-2017 in the United States, with 36 months of continuous insurance coverage. Patients treated with hematopoietic cell transplantation were excluded. Inpatient and outpatient utilization and cumulative reimbursements (inflation-adjusted to December 2020) were computed 8 and 36 months from diagnosis and stratified by age (1-9, 10-12, and ≥ 13 years) as proxies for National Cancer Institute risk groups. Regression models were constructed to assess associations with demographic and clinical characteristics. RESULTS: Among 927 patients (median age, 6 years; interquartile range, 3-12 years; 43% female), individuals age ≥ 10 years had 23-25 more inpatient days and 22 more outpatient encounters compared with younger patients. The 36-month median cost was $394, 000 (USD) (interquartile range, $256, 000-$695, 000 [USD]), and 64% of the total cost was incurred during the initial 8 months. The 36-month cost was 1.5-fold higher for those age 10-12 years and 1.7-fold higher for those age ≥ 13 years compared with 1-9 years. The cost for those diagnosed in 2013-2017 was 70% higher compared with 1993-2002, and was not different on the basis of sex, race, or ethnicity. CONCLUSION: Older age was associated with higher utilization and cost, and the cost of treatment increased significantly over time. These data provide valuable benchmarks for future studies examining the cost-benefit of ALL therapy modifications.